Analisis Sistem Antrean Pelayanan Administrasi Pasien di Klinik dr. Asih Krustiyani, Probolinggo, Jawa Timur - Kharis, Selly Anastassia Amellia (Publisher : Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
The discussion taken in this research is